TB diagnostics in India: creating an ecosystem for innovation. (January 2012) - Engel, Nora; Kenneth, John; Pai, Madhukar
The 'TB diagnostics in India: from importation and imitation to innovation'' conference was held in Bangalore, India, on 25–26 August 2011, and was organized by the St. John''s Research Institute, Bangalore, with the support of several partners. This unique conference brought together, for the first time, over 220 representatives from industry, government, donors, academia, civil society and the media to discuss what it takes to innovate in tuberculosis (TB) diagnostics in India. The goal was to engage these stakeholders to stimulate interest and investments in TB innovations. The conference was successful in engaging stakeholders and understanding the challenge of TB innovations from diverse perspectives. Coordination between stakeholders and innovations in delivery systems, partnerships, funding, regulatory and communication mechanisms are among the key challenges ahead.